PENGGUNAAN METODE NUMBERED HEAD TOGETHER (NHT) DAPAT MENINGKATKAN HASIL BELAJAR MATERI PERSAMAAN KUADRAT PADA SISWA KELAS IX/2 SMP NEGERI 1 BANDAR DUA - Mardhiah (FITRAH: International Islamic Education Journal, 2021)
Lack of enthusiasm, lack of activity, less student-centred class, and sometimes people playing alone in class, are problems faced by SMP Negeri 1 Bandar Dua, Pidie Jaya Regency, especially for mathematics for grade IX students. /2, The bad impact is their mastery of concepts and their learning completeness is 60% . This condition is certainly not expected in the teaching and learning process. This research was carried out in the form of Classroom Action Research (CAR) at the junior high school level, which was carried out at SMP Negeri 1 Bandar Dua. The purpose of this study was to improve learning outcomes for the Quadratic Equation Material in Class IX/2 SMP Negeri 1 Bandar Dua. The results showed that: 1. Mathematics learning by integrating quizzes into the numbered-head-together cooperative learning model can increase student activity in groups, do assignments, think together, and answer quizzes. 2. Mathematics learning by integrating quizzes into the numbered-head-together cooperative learning model can improve student learning outcomes for class IX/2 SMP Negeri 1 Bandar Dua, Pidie Jaya Regency. 3. Student response to mathematics learning that integrates quizzes into the numbered-head-together cooperative learning model is positive.